A new 2% testosterone gel formulation: a comparison with currently available topical preparations. (30th March 2018) - Arver, S.; Stief, C.; de la Rosette, J.; Jones, T. H.; Neijber, A.; Carrara, D.
Summary: Testosterone gel formulations have become a popular testosterone replacement therapy in patients with hypogonadism since their advent in the year 2000. The gel formulations restore testosterone levels to mid‐normal physiological levels (14–17.5 nmol/L) as early as within 24 h, and help alleviate the signs and symptoms of testosterone deficiency, thereby leading to an improved quality of life. Although testosterone gels have a favourable efficacy and safety profile as compared to injectable and patch formulations, risk of secondary exposure poses a challenge. Approved testosterone topical formulations include Tostrex ® (Tostran ®, Fortesta ® ), Androgel ® (Testogel ® ), Testim ® and Axiron ® (solution), which have a favourable efficacy profile and positively impacted patient‐reported outcome(s). Besides, Testavan, which is a 2% testosterone gel, is under registration in Europe and already approved in Australia in May 2017. Testavan uses a novel hydroalcoholic and highly viscous topical formulation. This product comes with a metered dose dispenser and a cap applicator that allows a hands‐free application for precise dispensing and application. The present article provides a comprehensive review of pharmacokinetic, tolerability and safety profile of the testosterone gels available in the market along with the new 2% testosterone gel, Testavan.